Impact of Clean Intermittent Catheterization on Renal and Lower Urinary Tract Outcomes in Spinal Cord Injury Patients - Irfan Elahi, Musab Umair Khalid, Bilal Javaid, Samee Ullah Khan, Fazl-e-Mateen, Muhammad Nouman Khan, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Neurogenic bladder dysfunction following spinal cord injury (SCI) is a major source of morbidity,predisposing patients to recurrent urinary tract infections (UTIs), renal deterioration, andcompromised quality of life. Clean intermittent catheterization (CIC) is widely recommended asthe gold standard for bladder emptying in this population